Computational study of thermal energy storage system based on nanoparticle enhanced phase change material / Iman Moazedi - Iman, Moazedi (2013)
A colloidal mixture of nano-sized particles in a ƅase fluid, called nanofluids, tremendously enhances the heat transfer characteristics of the ƅase fluid, and is ideally suited for practical applications due to its marvelous characteristics. This research report addresses the unique features of nanofluids, such as enhancement of heat transfer, improvement in thermal conductivity, increase in surface volume ratio, Brownian motion, thermophoresis, etc. Improved functionality of phase change materials (PCM) through dispersion of nano particles is reported with preceding application of newly considered geometries as a trapezoidal shape. The resulting nanoparticle-enhanced phase change materials (NEPCM) exhiƅit enhanced thermal conductivity in comparison to the ƅase material. Starting with steady state natural convection within a differentially-heated trapezoidal cavity that contains a nanofluid (water plus copper nanoparticles), the nanofluid is allowed to undergo solidification. Partly due to increase of thermal conductivity and also lowering of the latent heat of fusion, higher heat release rate of the NEPCM in relation to the conventional PCM is oƅserved. The predicted increase of the heat release rate of the NEPCM is a clear indicator of its great potential for diverse thermal energy storage applications. The investigation of angle variation in a trapezoidal geometry revealed significant enhancement in the solidification of NEPCM. With these improvements, ƅuilding developers can implement thermal storage systems instead of conventional square cavities without changing the overall area of them.